Perception of academics from the Departament of Medical Sciences of the Faculty of Medicine and Dentistry ofe the University of Antofagasta on the importance of formative research in medical education - Torres Belma, Alberto; Becerra Mellado, Natalia; Gutiérrez Pereira, Bárbara; Alvarez Iguaín, Claudia (Spanish Journal of Medical Education, 2024)
Formative research consists of the development of research skills in students. This implies the existence of a teacher who has the necessary skills in the area [1]. The general objective of the research was to describe the perception of academics from the Department of Medical Sciences of the Faculty of Medicine and Dentistry of the University of Antofagasta about the importance of formative research in medical education. Descriptive and cross-sectional study that included 27 academics out of a total of 42 (64.2%). The questionnaire was structured in the following dimensions: formative research in medical education and teaching strategies; and activities related to formative research. The response category “Very important” obtains the highest value (54%) in the statement that consulted about the Development of research skills in medical students during their undergraduate training. The response category “Very important” records the highest value in the statement that consulted on Discussion of clinical cases (79%). Academics value formative research, in accordance with the requirements of the National Accreditation Commission of Chile (CNA), recognizing the role of different milestones, actors involved and teaching strategies.